Management of forgotten double-J stent in a tertiary care center with ten years of experience: a retrospective study - Mahmood, Khalid; Singh, Kamalkant Harishankar; Upadhyay, Rohit; Kumar, Vijoy; Kumar, Amit; Singh, Deelip K. (International Surgery Journal, 2020)
Background: Forgotten double-J (DJ) stents is documented commonly in urological cases with consequences varying from encrustation, UTIs, pyelonephritis, hydronephrosis and non-functioning kidney. This study aimed to present the experience of managing patients with forgotten DJ stents (>3 months) over a period of ten years. Methods: The study conducted a retrospective review of patients with forgotten DJ stents from January 2009 to December 2019. The details reviewed included indications for stent placement, indwelling time, presenting complaints, reason for non removal, radiological investigations, management techniques, and complications. Results: 52 patients with forgotten DJ stents for >3 months were reviewed. Mean age was 32.1 years. The majority were literate (73.1%). Ureteroscopy was the most common primary surgery performed (53.8%). The mean indwelling time was 38.96 months. Presence of the ureteric stone, bladder stone, and renal stone was observed in 45 (86.5%), 42 (80.7%), and 28 (53.8%) patients, respectively. The DJ stent was fragmented in 13.4% of the patients. The commonest complaints were pain (88.4%) and dysuria (63.4%). The stents were managed by combinations of various endourological techniques including cystoscopic stent retrieval (CPE), PCNL, URSL, ESWL with cystoscopic stent retrieval, PCLT (percutaneous cystolithotripsy). Cystolithotomy was used for very large bladder stones. Nephrectomy was needed in 2 cases due to nonfunctional kidneys while one required open ureterolithotomy and stent retrieval after failure of endoscopic approach. Conclusions: Forgotten DJ stents have severe consequences and management approach requires combination of various endourological procedures with ESWL, URSL, PCNL, open ureterolithotomy and cystolithotripsy.